(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article highlights the didactic opportunities and pedagogical significance of the 5E model in organizing effective mathematics lessons in primary education. The study analyzes the role of the 5E instructional model, consisting of the stages Engage, Explore, Explain, Elaborate, and Evaluate, in developing students’ mathematical thinking, independent reasoning, and practical competencies. During the research process, observation, pedagogical experiment, interview, and comparative analysis methods were used. The results showed that mathematics lessons organized on the basis of the 5E model increase students’ interest in learning, develop their logical thinking skills, and create opportunities to connect theoretical knowledge with practice. In particular, the use of interactive methods and problem-based situations in developing mathematical competencies among primary school students ensures high effectiveness. The study concludes that integrating the 5E model with modern educational technologies contributes to improving the quality of primary mathematics education.